Entrecruzamento de vozes na constituição do discurso : um diálogo possível entre Bakhtin e Ducrot - Frossard, Elaine Cristina Medeiros (2008)
This research, included in a socio-enunciative language perspective, has as its general aim to put into discussion the subject of enunciation unicity and to investigate the voice crossing in the speech constitution. Benveniste is taken as a starting point to direct the theoretical formulation based on Bakhtin’s Dialogism Theory, in association with Ducrot’s Polyphonic Theory, this one deriving from the Argumentative Semantics. It is proposed, in this way, an approach between Bakhtin and Ducrot, admitting that, although situated in different theoretical places – the first one reflecting on the social-historical-ideological dialogue between utterances, in the speech; and the second investigating marks of polyphony present in the utterances internal structure – these two authors prioritize the speech in the determination of the meaning, so they can be called, without theoretical incoherence, to explain the enunciative heterogeneity. In order to proceed with an analysis sample, it was selected a news article about the civil crisis in Brazilian aviation, expecting that the social-historical forces which act in the determination of the news article genre would favor the expression of an enunciative polyphony. The parameters proposed to the analysis allowed to show the speech dialogic constitution as a whole, as well as to identify marks of polyphony in the utterances present in the argumentative link of the text.